Element abundances in stars: connection with chemical evolution of a Galaxy - Mishenina, T. V. (Одеські астрономічні публікації, 2017)
Abundaces of 17 elements in the atmospheres of 100 stars belonging to different population of the Galaxy were determined. The comparing of the obtained results with the predictions of current chemical evolution models was made.